Monitoring data of electrokinetic stabilisation method for soft clay using EKG electrode - Ahmad Tajuddin, Saiful Azhar (2014)
Electrokinetic Stabilisation (EKS) method has the potential to overcome problems on highly compressible clay. This study presents the monitoring results from an experimental study of EKS on soft clay soil. Inactive kaolinite clay, inert electrode and distilled water (DW) were used as a pure system mechanism before any chemical stabilisers will be used in this research. Therefore, this monitoring data will provide a baseline study to improve efficiency of the EKS approach for ground improvement application. The test model were used inert electrodes of Electrokinetic Geosythentic (EKG) developed at the Newcastle University to apply a constant voltage gradient of 50 V/m across a soil sample of 400 mm length. The distilled waters were used at the pore electrolyte fluid compartments and supplied under zero hydraulic gradient conditions for periods of 3, 7 and 14 days. Throughout, monitoring data of electric current for all treatments were measured. Results showed that the electric current trend in this pure system was attributed to the electrochemical effects in the clay-water electrolyte system